2012
DOI: 10.1111/j.1573-7861.2012.01359.x
|View full text |Cite
|
Sign up to set email alerts
|

Penny for Your Thoughts: Beggars and the Exercise of Morality in Daily Life1

Abstract: Urban sociology has tended to study interactions between passersby and ''street persons'' with an emphasis on the ways street persons become bothersome, harassing, or dangerous. This article moves away from the focus on the ways interactions in public go awry and focuses on how individuals account for the mundane, everyday exchanges they have with strangers who seek their help. Based on interview data (N = 31) and qualitative analysis of data from an Internet survey (N = 110), this article suggests that the pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 55 publications
(46 reference statements)
2
16
0
Order By: Relevance
“…Our participants expressed distrust of large organizations and concerns over appropriate use of donations appears to be consistent with concerns over appropriate donation use and desire for donor control (Aptekar ; Dromi ; Glanville et al ) reflected in the giving literature more broadly. The convenience of the process and its ability to serve as a mechanism for accomplishing other goals offers another parallel between our findings and patterns in nondisaster giving (Aptekar ).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Our participants expressed distrust of large organizations and concerns over appropriate use of donations appears to be consistent with concerns over appropriate donation use and desire for donor control (Aptekar ; Dromi ; Glanville et al ) reflected in the giving literature more broadly. The convenience of the process and its ability to serve as a mechanism for accomplishing other goals offers another parallel between our findings and patterns in nondisaster giving (Aptekar ).…”
Section: Discussionsupporting
confidence: 74%
“…Research on Freecycle giving—a movement to give away items through a network, with the intent of keeping goods out of landfill—reveals that the people giving away items had certain expectations of how donations would be used and how recipients would act, and they exercised control over the donation and recipient by using these criteria in their decisions around giving their unwanted items (Aptekar ). In Dromi's () study on giving to street beggars, some participants revealed efforts at trying to ascertain how monetary donations would be used, viewing only some uses as acceptable. When they feared money would be used in ways donors saw as inappropriate, they sometimes turned to offering other forms of support (Dromi ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Dromi (2012) offered an alternative analysis. He stated that beggars are not symbols of the negative dimension of the urban condition---that is threatening, frightening, stressful, and manipulating people to obtain benefits---rather their existence should be interpreted as "another valuable hue" in urban life.…”
Section: Psychology Of Begging Behavior and Its Social Dimensionsmentioning
confidence: 99%
“…Begging is the practice of imploring others to grant a favor, often a gift of money, with little or no expectation of reciprocation [1]. It means soliciting or receiving alms in public place, whether or not under any pretense such as singing, dancing, fortune telling, reciting holy verse or performing tricks; entering in any private premises for the purpose of soliciting or receiving alms; exposing or exhibition with the object obtaining or extorting alms any sore would, injury deformity or disease; having no visible means of subsistence and wandering about and remaining in any public place in such condition or manner as makes it likely that the person doing so exists by soliciting or receiving alms; and allowing oneself to be used as an exhibit for the purpose of soliciting or receiving alms under the provisions of Bangladesh Children Act, 1974, Section 2 (c) [2].…”
Section: Introductionmentioning
confidence: 99%